Fulminant Clostridium difficile Colitis: Comparing Computed Tomography with Histopathology: Are They Concordant?. Issue 10 (October 2014) - Felder, Seth I.; Larson, Brent; Balzer, Bonnie; Wachsman, Ashley; Haker, Katherine; Fleshner, Phillip; Annamalai, Alagappan; Margulies, Daniel R.
A Total abdominal colectomy (TAC) is recommended for fulminant Clostridium difficile colitis (FCDC) because intraoperative assessment of diseased segments is inaccurate. To determine whether computerized tomography (CT) provides an accurate assessment of disease, we examined the concordance between CT and histopathologic colitis distribution in patients undergoing TAC for FCDC. The ileocolon was divided into seven distinct segments. Of 20 patients meeting criteria, the median interval between preoperative CT and TAC was 1.5 days (range, 0 to 23 days), and mortality was 65 per cent. The CT distribution of colitis was pancolitis in 12 patients and segmental in eight. Nine of the 12 patients with CT pancolitis had histologic pancolitis (75% concordance). Four of the eight patients with CT-diagnosed segmental disease had histologic segmental disease (50% concordance). For patients with FCDC, the distribution of colitis on CT agrees with the histopathologic extent of disease in the majority of patients. However, discordance between CT and histologic extent of disease was present in 25 to 50 per cent of patients. Therefore, the recommendation for TAC rather than segmental resection for FCDC remains justified.